Ismaili and other Arabic manuscripts : a descriptive catalogue of manuscripts in the Library of the Institute of Ismaili Studies /: a descriptive catalogue of manuscripts in the Library of the Institute of Ismaili Studies. (2000) - Unknown
No abstract available